In vitro regeneration responses of Callus of Catharanthus roseus (L) G.Don. to plant growth regulators and chitosan treatments - Gandoh, Norhafizah (2015)
The present study was conducted to establish in vitro regeneration responses of callus of Catharanthus roseus to chitosan treatments in combination withPGR (IBA+NAA). Leaf petioles from 5 weeks old plants were used as explant callus initiated was cultured on half MS (Murashige and Skoog, 1974) media containing PGR and different concentrations of chitosan. The callus was cultured in medium supplementedwith (0, 1, 2, 3, 4 and 5 mg/L) chitosan in 16 treatments combination of IBA and NAA each with(0, 1.5, 3.0, and 4.5 mg/L). The parameters used to access growth and development of callus was number of roots, length of roots and dry weight of callus. The experiment was conducted in a complete randomized design (CRD) in 3 replications. Medium containing 5 mg/L chitosan shows high dry weight of with 0.786 g and treatment with 2 mg/L of chitosan gavethe highest number and longest length of roots with 53.66 and 2.47 cm respectively. The study shows positive effects of chitosan on C. roseus.